Risk Factors Related to Low Birth Weight in Cienfuegos Municipality - Juan Rafael Zerquera Rodriguez; Yusimi Cabada Martínez; Delia Zerquera Rodríguez; Hilda María María Delgado Acosta (Medisur)
Background: the low birth weight still constitutes a complex a complex health problem. It is determined by some factors and it is the most important predictive index of infantile mortality. Objective: identifying the risk factors related to low birth weight. Methods: a descriptive study was conducted. There were analyzed the 77 birth of children with inferior weigh to 2500g, occurred in 2010 at the municipality of Cienfuegos, puerperas were included, mothers of those children. The pregnancy's follow-up cards, patient’s clinical records and municipal and provincial statistics were checked. In addition to the socio-demographic characteristics, the nutritional state, numbers of pregnancies, heavy profit during pregnancy, age, toxic habits and diseases correlated to pregnancy were analyzed. Results: the index of low birth weigh oscillated between 3.6 and 6.7 per month. The 52% of low birth weight newborn’s mothers had school university level. The 74 % of mothers work. The 70.1 % were smokers and the 57, 1 % developed a gravidum hypertensive disease. Conclusions: the most associated factors to low birth weight were, the mother’s habit to smoke, as well as the diseases that affected them during pregnancy, fundamentally the hypertensive disease and the vaginal sepsis.